What Makes a Better Life for People Facing Dementia? Toward Dementia-Friendly Health and Social Policy, Medical Care, and Community Support in the United States - Gaster, Barak (The Hastings Center report, 2024)
Taking steps to build a more dementia-friendly society is essential for addressing the needs of people experiencing dementia. Initiatives that improve the quality of life for those living with dementia are needed to lessen controllable factors that can negatively influence how people envision a future trajectory of dementia for themselves. Programs that provide better funding and better coordination for care support would lessen caregiver burden and make it more possible to imagine more people being able to live what they might consider a "good life" with dementia. Specific proposals, such as payment for dementia care managers and new systems to support high-quality, symptom-based palliative care beyond the hospice benefit of only six months, would improve and reframe how many people in the United States experience a dementia illness. Such changes should be incorporated into discussions about improving and respecting preferences in the later stages of dementia.